Stakeholder Participation in Growing Spirit of Saving for Children in Beji Timur, Depok - Kartika Nuringsih; Khairina Natsir (Journal of Innovation and Community Engagement, 2021)
In line with the Indonesian money-saving campaign, community service activities were carried out to foster interest in money-saving among kindergarten students in Beji Timur, Depok. These activities had been carried out since the end of March and ended in June 2021 as the culmination of the theme “Ayo Menabung”(let's save money), with the target audience of Raudhatul Athfal Toufiqurrahman students. The community service partner was BRI Agroniaga Depok Branch which provided facilities for opening student saving accounts and sponsoring other educational activities. A total of 32 saving accounts had been realized, and in June 2021, the peak of the “Ayo Menabung” event was held in the form of the practice of money deposit in a bank. Each student has an account opened with an initial deposit of IDR.20,000, then in the practice of saving, each student was given IDR.200,000 to be deposited in their accounts. During the evaluation period, another IDR.30,000 was added, so that each student had a total saving of IDR.250,000. As a continuation, the children would maintain their savings account independently, facilitated through a pick-up service from the bank, supported by motivation from parents and teachers to keep the children's consistency in saving money. Because it was still in a pandemic situation, bank tellers or customer service staffs would come to school to serve the children practicing money deposit. Through this community service, the children got new knowledge about banking and the benefits of savings. In addition, it also provided financial knowledge to the parents and teachers. There was almost no significant problem in the implementation of the service activities, except for the constraints more related to the Covid-19 pandemic so that there was a necessary extra effort for activities to coordinate related parties. The commitment and participation of stakeholders in information dissemination and actualization of student money-saving practices can foster a culture of money-savings while the collaboration creates a mechanism to ensure sustainable money-saving habit among children.